UiTM examination attendance using quick response (QR) code / Aiman Nurrasyid Shahrul Kamil - Shahrul Kamil, Aiman Nurrasyid (Faculty of Computer and Mathematical Sciences, 2018)
In these day, UiTM still using traditional method in student attendance during examination. However, this old method make student to right down their information and make them take time on fill up the examination attendance slip. Next, invigilator also need more time to take student attendance and check student information by taking student exam slip and check with student’s matric card. Therefore, Quick Response (QR) code is used to make the process more reliability and faster to take student attendance and monitor the student who didn’t attend to the class or examination. Next, QR code is use in the examination to make the invigilator easier to use and make the process of taking student attendance faster. This project use SDLC method that perform waterfall method to make the phase of the project run smoothly and manageable. This project also used image recognition method to scan the QR code either horizontal or vertical. Based on testing that already conducted the application is run smoothly without having any error or bug. On the other hand, student also agree that QR code is easier, because student didn’t require to write their information on the paper instead just bring the QR code along to the examination hall. User of this application also agree that this is easy to understand and use. In conclusion, this project can make the user easier on taking exam attendance to make the process of taking attendance more faster and reliability. For future recommendation, this project need to add some features that can notify the absent student to give letter of reason to HEA staff after the exam by using email and message to the student.